Biotechnological production of terpenoids using cell factories - Si, Yalan; Li, Shasha; Chen, Chen (Frontiers in Pharmacology, 2025)
Terpenoids, as one of the most abundant natural products in nature, have important application values in the fields of medicine, food, and daily chemicals industries. Beyond their industrial applications, terpenoids offer notable nutritional benefits to humans and are extensively utilized for their pharmacological properties. Conventional production approaches, such as plant extraction and chemical synthesis, are increasingly constrained by limited resources and environmental concerns. Consequently, biotechnology has emerged as a pivotal strategy for terpenoid synthesis, owing to its advantages in efficiency, sustainability, and precise regulatory capabilities. This review provides a comprehensive overview of recent progress in biotechnological production of terpenoids, with a particular emphasis on metabolic and enzyme engineering and enzyme engineering. Furthermore, we explored the potential of using computational and artificial intelligence technologies for the rational design and construction of high-performance cell factories is discussed, providing promising pathways for the biosynthesis of terpenoids in the future.